Nursing Students\' Time Management: Directing Activities - Tayebe Mirzaei; Fateme Oskouei; Forough Rafii; Ali Ravari (Iran University of Medical Sciences, 2015)
Background: The nursing students should acquire practical and theoretical competence required for the patients' care during their 4 years of education. This involves proper use of time. The purpose of this study was to investigate how nursing students manage their time despite the academic difficulties and obstacles. Methods: This qualitative study was carried out through grounded theory method. The study population consisted of nursing students. Twenty-one nursing students studying at undergraduate level were selected purposefully for participation in this study. The data were collected with semi-structured interview and analyzed through Strauss and Corbin method (2008). MAXQDA 10 software was employed to organize and process the data. Results: Core variable of this study was "directing activities toward personal goals," representing in 3 behavioral patterns. The behavioral pattern of "retaliation from field" was one of the 3 patterns applied by nursing students. The properties of this pattern included "unknowingly entrance to nursing field," "stress and dissatisfaction with spending time," "nonacceptance of field," "attempt to decrease stress and obtain satisfaction," and "ignoring academic responsibilities". According to this pattern, the students spent most of their time on non-academic responsibilities while trying to overcome the stress. Conclusion: The findings of this study recommend the necessity for revising the admission method of nursing students and informed choice of nursing field by these students.